Roles of the lipopolysaccharide biosynthesis-related gene HP0858 in the fitness of Helicobacter pylori and its virulence in Galleria mellonella - Tram Thi Hong Nguyen; Pei-Chun Chen; Po-Chuan Wang; Wen-Han Wang; Chung-Yu Lan; Steffen Backert; Mou-Chieh Kao (Virulence)
Helicobacter pylori is a pathogenic bacterium associated with the development of gastric cancer and other gastric disorders. One of its major virulence factors, lipopolysaccharide (LPS), plays a crucial role in maintaining bacterial integrity, mediating host adhesion, and modulating the immune response. Recent studies have indicated that ADP-heptose, an intermediate in the heptose biosynthetic pathway involved in the LPS synthesis cascade, is a novel pathogen-associated molecular pattern for H. pylori. This study focuses on the HP0858 gene, which is predicted to encode RfaE/HldE, an enzyme with kinase and ADP-transferase activities essential for heptose production. An HP0858 gene-disrupted mutant was first generated, and the resulting mutant exhibited a truncated LPS structure, confirming its role in LPS biosynthesis. The HP0858-deficient mutant displayed increased sensitivity to the detergent SDS and the antibiotic novobiocin, heightened surface hydrophobicity, and a propensity for autoaggregation. Additionally, the mutant exhibited reduced adhesion and internalization capabilities, a diminished elongation phenotype, and failed to induce IL-8 secretion in infected gastric AGS cells. In an in vivo Galleria mellonella infection model, the HP0858 knockout mutant showed significantly attenuated virulence, as no bacterial load was detectable in the larvae’s hemolymph 48 h post-infection, unlike the wild-type strain. Finally, we provided evidence that the enzyme encoded by HP0858 is involved in a general protein glycosylation system linked to LPS biosynthesis, specifically glycosylating the adhesin AlpA. These findings highlight the essential role of RfaE/HldE/HP0858 in LPS biosynthesis and bacterial virulence, making it a promising target for future therapeutic interventions against H. pylori infections.